Psychometric Properties of the Lesbian, Gay, and Bisexual Identity Scale–Turkish (LGBIS-TR). Issue 12 (15th October 2017) - Kemer, Gülşah; Demirtaş, Ezgi Toplu; Pope, Amber L.; Ummak, Esra
ABSTRACT: The aim of the current study was to examine the psychometric properties of the Lesbian, Gay, and Bisexual Identity Scale (LGBIS; Mohr & Kendra, 2011) in a Turkish sample. Three hundred and ten LGB individuals participated and completed the Turkish version of the LGBIS (LGBIS-TR) along with the Satisfaction with Life, Positive and Negative Affect, and Self-Compassion Scales. Confirmatory factor analysis results yielded a good-fit for eight subscales of the LGBIS-TR. We also obtained satisfactory criterion validity and internal consistency reliability. Based on this initial study, the LGBIS-TR appears to be a psychometrically sound instrument to gauge LGB individuals' identity experiences in Turkey. We discuss the results along with previous findings and limitations of the study, and we provide implications for further research and practice.